Capture of gaseous and fine particulate pollutants emitted in the biomass post-combustion process - Costa, Maria Angélica Martins [UNESP]; de Souza, Alexandre Jorge Duarte [UNESP]; Mello, Bruna Sampaio [UNESP]; de Oliveira, Eliza Almeida [UNESP]; Oliveira, Lucas Freitas [UNESP]; Albini, Geisa [UNESP]; Sarti, Arnaldo [UNESP]; Dussán, Kelly Johana [UNESP] (Springer Nature, 2025)
Purpose: Emissions of gaseous pollutants, particularly carbon dioxide (CO2) and particulate matter, are increasing, primarily due to anthropogenic combustion of conventional fossil fuels. These emissions drive global warming and climate change, contributing to significant environmental and health impacts. This scenario highlights the urgent need for cleaner energy solutions, prompting industries and power plants to transition rapidly to sustainable sources such as biomass. While biomass combustion is carbon neutral regarding atmospheric CO2, it still generates particulate matter that must be controlled. Integrated strategies for CO2 capture, sequestration, storage, and utilization, along with effective particulate capture, are essential for reducing greenhouse gas emissions and minimizing health risks. Aim: This study primarily evaluates laboratory- and pilot-scale technologies for mitigating industrial CO2 and fine particulate matter emissions from biomass combustion. Methods: Emissions of gaseous and particulate pollutants were evaluated using a pilot burner. Initial CO2 capture tests were performed in a laboratory absorption column, followed by biomass combustion evaluations using a Venturi scrubber for gas capture and particulate removal. Results: The results indicated low CO2 capture efficiencies without chemical reactions. When a NaOH solution was used for chemical absorption at flow rates of 1.4, 1.8, and 2.0 L/min, capture efficiencies improved to 10.3, 10.4, and 17.24%, respectively. The Venturi scrubber effectively captured particulate matter but was less effective for CO2, although it performed well in capturing CO and NOx gases. Conclusion: Emissions of gaseous pollutants and PM were significantly high during the burning of biomass, such as sugar cane bagasse. The results showed high capture efficiencies for PM below 1.0 μm, reaching values above 80%. Advancements in capture technologies can help industries transition to sustainable practices, addressing both climate goals and air quality standards.
Keywords: Air pollution; Biomass; CO2 capture; Energy